Technological Aspects for Cryopreservation of Enzyme-Based Biosensors - Nardid, Oleg A.; Mangasarov, Dmitriy O.; Schetinskiy, Miroslav I. (Problems of Cryobiology and Cryomedicine, 2013)
Basing on the proposed approaches for storage of enzyme-based biosensors a technological process was developed, which allowed rapid and easy freezing, storage and warming of these devices. To do this we designed and produced the samples of containers, holder-cassettes, equipment for freezing according to the needed regimens. The produced equipment was involved to creation of technology for long-term storage of miniature glucose oxidase-based electrochemical biosensors. Probl Cryobiol Cryomed 2013; 23(4):338–346.